GERILYA AS ALTERNATIVE LITERACY PROGRAM GROW INTEREST STUDENT APPRECIATE POETRY - Rahayu, Ira; Yulla Hidayah; Khalimi Romansyah (Cirebon International Conference on Education and Economics Proceeding, 2024)
Literacy is a means for students to recognize, understand and apply the knowledge they gain at school. In this case, poetry writing skills are a necessary part of literacy owned student so that need get attention more on learning process or outside class hours. The formulation of the problem in this research is (1) knowing the interest of SMPN 2 Sumber students in appreciating poetry and (2) knowing the response of SMPN 2 Sumber students to the implementation of Gerilya as an alternative literacy program in fostering interest in appreciating poetry and (3) describing the form of appreciation of SMPN 2 students Source for writing poetry after participating in Gerilya activities. The research method uses descriptive qualitative research. This research aims to find out how far Gerilya as alternative program literacy grow interest students appreciate poetry. This research uses descriptive research with method quantitative. Technique collection data in study this is by interviews, questionnaires, and tests. The result of this research is the lack of student interest in appreciating poetry because there are difficulties faced by students when writing poetry. After implementing the Gerilya program, the results showed that students' interest in appreciation poetry increase. Besides That, there is analysis poetry students' work by paying attention to several aspects, namely: suitability of the theme to the content of the poem, word choice, rhyme, atmosphere and message contained in the poems so that in this research Gerilya can be an alternative literacy program to foster students' interest in appreciating poetry.